Flexible, large-area, multi-layered graphene/cellulose composite for dye filtration applications. (March 2022) - H.S., Vishwanath; M.P., Shilpa; S.C., Gurumurthy; Gedda, Murali; Ramam, Koduri; Eshwarappa, K.M.; Kirana, Ravi; Mishra, Nirankar Nath; Mundinamani, Shridhar
Abstract: Textile and clothing industry effluents are the primary source of water pollution, affecting aquatic animals and plants. The need of the hour is to filter these effluents to avoid contamination. Nanofiltration using carbon-based membranes is an effective method in dye filtration. The present work describes graphene oxide (GO) and reduced graphene oxide (RGO) coated cellulose surfaces for dye filtration. These sheets exhibited high porosity, large surface area, high flexibility, inexpensive, easy to fabricate, and successfully employed for efficient nano dye filtration. The novelty of the present work is the filtration of most industrially used dyes such as methylene blue and rose bengal. Results confirm the filtration up to 98% and 94% for both Methylene Blue (MB) and Rose Bengal (RB) dyes, respectively, and the eco-friendly mode of treating industrial dye-contaminated water. Graphical Abstract: ga1 Highlights: Facile synthesis of graphene and its deposition on the skeleton of cellulose. GO deposited cellulose is reduced using hydrazine hydrate vapors. GOC and RGOC are used to filter the rose bengal and methylene blue commonly used industrial dyes. Results confirm the filtration up to 98% and 94% for Methylene Blue (MB) and Rose Bengal (RB) dyes, respectively.